Factors Influencing Job Satisfaction in Information Technology Professionals in India - Meetali Saxena, Deepika Pandita (International Journal of Advanced Science and Technology, 2020)
In this rapidly changing world today, employees in the tech industry in particular are presented with a wide range of opportunities to change their current job. In addition, variables at work such as a challenging work climate, equitable distribution of rewards, positive work environment, supporting peers, etc. play a major role in maintaining the long-term association between an individual and the company. Such variables may be listed as job satisfaction factors. The paper has analysed the previous research papers to find out what other researchers have done for ensuring the job satisfaction of the employees in various industries. In 1967, Weiss Dawis and Lofquist developed the short version of Minnesota Satisfaction Questionnaire (MSQ) having a 5 point Likert-type scale with 20 items. This questionnaire is commonly used in numerous research work, as it is a well-established and a stable scale over a long time with proven results. The author has used the short form of the Minnesota Satisfaction Questionnaire (MSQ) to gauge job satisfaction. The MSQ short form is the result of Vocational Psychology Research, The University of Minnesota who is the origin of this material. The data is analysed and studied in depth using correlation to find out what factors play a significant role in work satisfaction among IT employees. The author has come to the conclusion that various intrinsic factors and extrinsic factors affect the overall job satisfaction of an employee. The results can be incorporated by the Human resources department to bring changes in organisation and further help firms to discuss strategies to improve employee work satisfaction and thus productivity to achieve the objectives of the organisation in the long term.